2010 Seventh International Conference on the Quality of Information and Communications Technology 2010
DOI: 10.1109/quatic.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Abstract Testing: Connecting Source Code Verification with Requirements

Abstract: Abstract-Traditionally, test cases are used to check whether a system conforms to its requirements. However, to achieve good quality and coverage, large amounts of test cases are needed, and thus huge efforts have to be put into test generation and maintenance. We propose a methodology, called Abstract Testing, in which test cases are replaced by verification scenarios. Such verification scenarios are more abstract than test cases, thus fewer of them are needed and they are easier to create and maintain. Check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The fundamental reason behind it is to enhance fulfillment level of client alongside the nature of the software [9]. In this way, verification and validation of requirements are very crucial for the strongly fulfilled end client [13,23]. It has been observed that if a client discovers an issue, it will surely enhance the expense in incredible ways, whereas, through discovering an issue at the verification stage causes less cost [2,24].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental reason behind it is to enhance fulfillment level of client alongside the nature of the software [9]. In this way, verification and validation of requirements are very crucial for the strongly fulfilled end client [13,23]. It has been observed that if a client discovers an issue, it will surely enhance the expense in incredible ways, whereas, through discovering an issue at the verification stage causes less cost [2,24].…”
Section: Introductionmentioning
confidence: 99%